STUDI ADSORPSI LOGAM Pb PADA TANAH TERCEMAR ABU TERBANG (Fly Ash) DENGAN MENGUNAKAN TANAMAN KANGKUNG DARAT (Ipomoea reptans Poir) - Khairuddin; Yul Uca Sali Putri; Husain Sosidi; Dwi Juli Pusptasari (KOVALEN: Jurnal Riset Kimia, 2019)
Pb metal adsorption studies on land water spinach (Ipomoem reptans poir) have been carried out. The method of analysis was carried out using a completely randomized design with two independent variables, i.e amount of Pb metal concentration adsorb on the roots of land spinach and the lifetime of the land spinach roots. The results show that the amount of Pb metal adsorp on the land spinach roots with variations in the age of 2-5 consecutive weeks was 0,023 µg/g; 0,03 µg/g; 0,084 µg/g; 0,099 µg/g, respectively. The results of both statistical tests, F test and LSD test, show that there was a significant difference in the concentration of Pb in each age of harvest, which in the fifth week showed the highest Pb level. BCF test results show that Pb metal adsorption takes piace with a phytoextraction mechanism. Keywords: Absorption, Lead Metal, Land Weter Spinach, Pb Levels, Length Of Planting Time